Equine lentivirus counteracts SAMHD1 restriction by Rev-mediated degradation of SAMHD1 via the BECN1-dependent lysosomal pathway. Issue 10 (3rd October 2021) - Ren, Huiling; Yin, Xin; Su, Chao; Guo, Miaomiao; Wang, Xue-Feng; Na, Lei; Lin, Yuezhi; Wang, Xiaojun
ABSTRACT: The innate immune restriction factor SAMHD1 can inhibit diverse viruses in myeloid cells. Mechanistically, SAMHD1 inhibits lentiviral replication including HIV-1 by depleting the nucleotide pool to interfere with their reverse transcription. Equine infectious anemia virus (EIAV) is an ancient lentivirus that preferentially attacks macrophages. However, the mechanism by which EIAV successfully establishes infection in macrophages with functional SAMHD1 remains unclear. Here, we demonstrate that while equine SAMDH1 can limit EIAV replication in equine macrophages at the reverse transcription stage, the antiviral effect is counteracted by the well-known transcriptional regulator Rev, which downregulates equine SAMHD1 through the lysosomal pathway. Remarkably, Rev hijacks BECN1 (beclin 1) and PIK3C3 to mediate SAMHD1 degradation in a canonical macroautophagy/autophagy-independent pathway. Our study illustrates that equine lentiviral Rev possesses important functions in evading cellular innate immunity in addition to its RNA regulatory function, and may provide new insights into the co-evolutionary arms race between SAMHD1 and lentiviruses. Abbreviations :3-MA: 3-methyladenine; AA: amino acid; ACTB: actin beta; AD: activation domain; ATG: autophagy related; Baf A1: bafilomycin A1 ; BD: binding domain; BECN1: beclin 1; BH3: BCL2-homology-3 domain; BiFC: bimolecular fluorescence complementation; CCD: coiled-coil domain; class III PtdIns3K: class III phosphatidylinositol 3-kinase; CQ: chloroquine; Co-IP: co-immunoprecipitation; dNTPase: dGTP-stimulated deoxynucleoside triphosphate triphosphohydrolase; ECD: evolutionarily conserved domain; EIAV: equine infectious anemia virus; eMDMs: equine monocyte-derived macrophages; GFP: green fluorescent protein; HD: histidine-aspartic; HIV-1: human immunodeficiency virus-1; hpi: hours post infection; hpt: hours post transfection; KO: knockout; LAMP2: lysosomal associated membrane protein 2; LMB: leptomycin B; PMA: phorbol 12-myristate 13-acetate; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; ND: unknown non-essential domain; NES: nuclear export signal; NLS: localization signal; NS: statistically non-significant; PIK3C3: phosphatidylinositol 3-kinase catalytic subunit type 3; RBD: RNA binding domain; RT: reverse transcriptase; siRNAs: small interfering RNAs; SAMHD1: SAM and HD domain containing deoxynucleoside triphosphate triphosphohydrolase 1; SIV: simian immunodeficiency virus; VN: C-terminal residues of Venus 174 to 238; VC: N-terminal residues 2 to 173 of Venus